Physico-mechanical Properties of Unsaturated Polyester Resin Reinforced Maize Cob and Jute Fiber Composites. Issue 9 (2nd September 2022) - Ali, Jamila B.; Musa, Abubakar B.; Danladi, Abdullahi; Bukhari, Muhammad M.; Nyakuma, Bemgba B.
ABSTRACT: In this research, the composites of maize cob (MC)/unsaturated polyester resin (UPR) and composites of jute fiber (JF)/unsaturated polyester resin (UPR) were prepared using the hand lay-up technique. The study employed 5%, 10%, 15%, and 20% filler loadings for the preparation of the MC/UPR and JF/UPR composites. The composites were subsequently characterized to examine their mechanical and physical properties. The results reveal that the increase in percentage filler loading decreases the tensile strength, impact strength, flexural strength, hardness, and density, whereas the water absorption increases at higher filler loading. This observation could be ascribed to clumping, voids, and agglomeration formed during composites preparation for both fillers. The MC/UPR composite exhibited better flexural resistance of 31.41 Mpa to 28.88 Mpa compared to 25.72 Mpa to 22.14 Mpa for JF/UPR due to the excellent dispersion of MC, larger surface area, and intermolecular interactions between the particulate MC filler/matrix. The MC/UPR composites also exhibited higher density compared to the JF/UPR due to the larger surface area and reduced voids in the structure. Overall, the study demonstrated that the valorization of maize cob and jute fibers into composite materials is a sustainable and environmental approach to waste disposal and management.